Resting heart rate measurement in elite athletes during COVID-19 lockdown: The impact of decreased physical activity - Pla, R.; Bosquet, A.; Aubry, A.; Toussaint, J. F.; Sedeaud, A. (Sustainability, 2021)
The purpose was to observe the effects of a four-week lockdown on the resting heartrate (RHR) and well-being perception of elite swimmers. Twenty elite swimmers performed RHRmeasurements upon waking in supine and standing positions. Baseline values and those measuredafter four weeks of lockdown were compared. Swimmers completed a questionnaire on their trainingvolume and state of well-being. During the lockdown, swimmers reported a weekly mean physicalactivity of 10.4±3.6 h (an estimated reduction of 254% compared to their usual training volume).After four weeks of lockdown, RHR in the supine position increased by more than two beats perminute (58.8±8.2 vs. 56.5±7.4 bpm,p< 0.05). In the standing position, RHR increased by almost15 beats per minute (103.3±13.2 vs. 88.4±9.4 bpm,p< 0.0001). Fifty percent of these athletesexpressed a decrease in well-being. These results underline that the lockdown circumstances induceda large reduction in parasympathetic activity in elite athletes, which was associated with a decreasein training volume. This increase in RHR may reflect that a highatly strenuous environment andmaintaining a high level of physical activity in this population could be favorable to preserve physicaland psychological health.